Participatory action research and disability activism (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
This article centres on my dissertation in Arts, Festival and Cultural Management at Queen Margaret University, Edinburgh. It explored whether participatory action research is appropriate for aiding the formation of disability arts-based policy recommendations in collaboration with Scottish-based disabled artists. These recommendations were intended for Creative Scotland, the national public arts funding body. The article will explain why thisproject was chosen, revealing that the reasons were partly personal. My upbringing and educational background have created a resolute stance that disabled people are acutely disadvantaged by normative social constructs. As will be contended, the academic and creative realms are not exempt from the shortcomings of an ableist macro paradigm, and this has been central to the research. Some key findings and provisional policy recommendationswill be touched upon which suggest that Creative Scotland could learn from paying closer attention to disabled artists’ views, and models of good practice elsewhere. A core strand will rest on the interplay between structure and agency - the possibilities for personal agency within the structures of policy and politics. Whilst a central problem in undertaking the research was capacity, in particular the limited duration of the fieldwork, nonetheless the research model enabled unanticipated collaborations, and exposed progressive ideas and routes which, if taken, could potentially lead to enacting change. The article will consider personal reflections on the research and my role within it, uncovering both real and imagined experienced. In doing so, a reminder of the importance of connecting theory to practice surfaced, honing the pivotal qualities a community educator should aim for, namelyfacilitating dialogue and claiming democratic spaces.